2009
DOI: 10.1007/s12223-009-0043-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fungal cellulase gene in Lactococcus lactis to construct novel recombinant silage inoculants

Abstract: The facultative anaerobic bacterium Lactococcus lactis has been used as a host for expression of a gene isolated from the anaerobic rumen fungus Neocallimastix sp. The coding region of the cellulase gene was obtained from the fungus with the aid of polymerase chain reaction amplification. The gene was then transformed into pCT vector system and the constructed recombinant plasmid was introduced into two L. lactis strains (IL403 and MG1363) by electroporation. The gene encoding the fungal originated cellulase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Furthermore, the fibre fractions (ADF and aNDF) of the silage were reduced (P <0.05) with inoculation compared to the control. This supports other studies that reported a reduced fibre content with inoculation (Sanderson, 1993;Keady & Steen, 1994;Ozkose et al, 2009). In contrast, some researchers (Faber et al, 1989;Phillip & Fellner, 1992) did not observe a reduction in cell-wall fractions from inoculated silages compared to the control.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the fibre fractions (ADF and aNDF) of the silage were reduced (P <0.05) with inoculation compared to the control. This supports other studies that reported a reduced fibre content with inoculation (Sanderson, 1993;Keady & Steen, 1994;Ozkose et al, 2009). In contrast, some researchers (Faber et al, 1989;Phillip & Fellner, 1992) did not observe a reduction in cell-wall fractions from inoculated silages compared to the control.…”
Section: Resultssupporting
confidence: 88%
“…Our previous research with maize silage (Nkosi et al, 2009) and potato hash silage showed improved aerobic stability of silage with LB inoculation. Contreras-Govea et al (2011) reported a reduced non-protein nitrogen (NPN) concentration in ensiled alfalfa with LL inoculation, and Ozkose et al (2009) reported reduced fibre fractions in ensiled wheat straw with LL inoculation compared to the control. However, the latter studies were conducted under laboratory-scale conditions and the aerobic stability of the silage and the effects of the inoculated silage on animal performance were not determined.…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was reported for L. lactis strains transformed with a Neocallimastix sp. cellulase (48). The expression of genes coding for fibrolytic enzymes in lactobacilli is also of interest for the development of …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, L. lactis was transformed with a cellulase gene from the rumen fungus Neocallimastix sp. [74]. The recombinant L. lactis strain enhanced the digestibility of forage when used in ensiling experiments.…”
Section: O R F R O M T H E C H R O M O S O M E [ 7 2 ] I N L Plantarummentioning
confidence: 99%